THE INFLUENCE OF RETURN ON ASSETS, LEVERAGE, SIZE, AND CAPITAL INTENSITY ON TAX AVOIDANCE - Hendrik Maula; Muhammad Saifullah; Nurudin Nurudin; Faris Shalahuddin Zakiy (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This study aims to examine the effect of Return On Assets, Leverage, Size, and Capital Intensity to tax avoidance. The purpose of this study is to provide empirically evidance about the effect of Return On Assets, Leverage, Size and Capital Intensity to tax avoidance. The independent variables of this study are Return On Assets, Leverage, Size and Capital Intesity. The dependent variable is tax avoidance measured by Effective Tax Rate (ETR). The population in this study are 48 property and real estate companies listed in Indonesian Stock Exchange (IDX) in period of 2013–2017. Sample was collected by purposive sampling method, total 28 property and real estate companies were taken as study’s sample. Analysis method of this research used multiple regression. The result showed that the return on assets and leverage signifficant effect on the tax avoidance. While size and capital intensity does not signifficant effect of the tax avoidance. Keywords: Capital Intensity, Leverage, Return on Assets, Size, Tax Avoidance